Identification of Igf2bp1 gene family and effect on chicken myoblast proliferation. Issue 1 (1st January 2021) - Feng, Guang; Zhao, Jiarong; Lei, Jingjing; Wang, Ling; Wang, Shanshan; Zhang, Tao; Lu, Hongzhao
ABSTRACT: The function of Igf2bp1 regulated muscle development in Lueyang black-bone chickens is to be investigated. The insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) belongs to the family of single-stranded RNA-binding proteins (IGF2BP1-3). IGF2BP1 is abundantly expressed in a broad range of foetal tissues, but only in a limited number of normal adult tissues, and is involved in biological regulation processes, including cell proliferation, differentiation, metabolism and migration, especially in tumour cells. Recent study has reported Igf2bp1 was a key gene that regulated the body size of Pekin ducks. We found that the expression level of Igf2bp1 gradually decreased with age in the leg muscle of Lueyang black-bone chicken, but its function in chicken muscle development is unknown. Firstly, the evolutionary relationship of Igf2bp1 gene family was analysed in chicken. Additionally, Igf2bp1 -overexpressed myoblasts of Lueyang black-bone chicken were constructed. The results showed that Igf2bp1 plays a negative role in cell proliferation by the CCK8 and 5-ethynyl-2′-deoxyuridine assay. Moreover, Igf2bp1 inhibited myogenesis by detecting the myoblast proliferation markers of pax7, the expression of myogenic differentiation markers, MyoD, MyoG and Myf5 in myoblasts. Thus, Igf2bp1 can inhibit chicken myoblast proliferation and differentiation by regulating key gene expression of myogenesis, which is not conducive to the growth and development of skeletal muscle in Lueyang black chickens.